2014
DOI: 10.2134/jeq2014.05.0240
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen in Stored Poultry Litter: Uric Acid and Xanthine

Abstract: Laboratory incubations of four broiler litter (BL) samples at 30°C were performed to investigate the effect of water content on the decay of uric acid nitrogen (UAN) and xanthine nitrogen (XN). UAN and XN concentrations increased in all samples during a period of 1 to 8 d before declining for the remaining 30 d. The increases may be the result of guanine and adenine catabolism. The slopes of linear equations fit to the natural log of the observations from 16 sampling points over 38 d were compared using the GL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 28 publications
(42 reference statements)
2
2
0
Order By: Relevance
“…Variability in nitrogen concentrations in different litter sources is not unexpected, however, as numerous compositional, environmental, or managerial factors such as types of bedding sources used, ventilation, number of flocks reared, moisture, and humidity as well as temperature can affect nitrogen status ( 32 ). As reported earlier ( 8 , 30 , 33 ), uric acid increased in concentration as early as 3 days after the beginning of composting in the present experiments thereby adding support to the conclusion that the nitrogen in uric acid may exist in a reversible flux between the end products of uric acid degradation and uric acid synthesis as proposed by Mowrer et al ( 33 ). It seems reasonable to suspect that xanthine oxidase activity may catalyze the transformation of available purines to uric acid during the early, aerobic period of composting; however, it has been reported that xanthine oxidase activity may be inhibited by tannins ( 26 , 34 , 35 ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Variability in nitrogen concentrations in different litter sources is not unexpected, however, as numerous compositional, environmental, or managerial factors such as types of bedding sources used, ventilation, number of flocks reared, moisture, and humidity as well as temperature can affect nitrogen status ( 32 ). As reported earlier ( 8 , 30 , 33 ), uric acid increased in concentration as early as 3 days after the beginning of composting in the present experiments thereby adding support to the conclusion that the nitrogen in uric acid may exist in a reversible flux between the end products of uric acid degradation and uric acid synthesis as proposed by Mowrer et al ( 33 ). It seems reasonable to suspect that xanthine oxidase activity may catalyze the transformation of available purines to uric acid during the early, aerobic period of composting; however, it has been reported that xanthine oxidase activity may be inhibited by tannins ( 26 , 34 , 35 ).…”
Section: Discussionsupporting
confidence: 92%
“…Increased uric acid concentrations in the poultry litter would yield a valuable source of crude protein when used as a ruminant feedstuff. Uric acid concentrations in the poultry litter used in the two experiments of this study ranged from 0.33 (experiment 2) to 1.98 (experiment 1) μmol/g of litter dry matter (the equivalent of 56 to 332 mg/kg of litter dry matter, respectively) were considerably lower than reported by Mowrer et al ( 30 ) but were within the range reported earlier ( 31 ). Variability in nitrogen concentrations in different litter sources is not unexpected, however, as numerous compositional, environmental, or managerial factors such as types of bedding sources used, ventilation, number of flocks reared, moisture, and humidity as well as temperature can affect nitrogen status ( 32 ).…”
Section: Discussionsupporting
confidence: 72%
“…These reactions may be accompanied by the loss of excreta organic matter because some compounds, such as ammonia and carbon dioxide, are volatile. Shifts in the chemical compounds of poultry excreta are initiated immediately after voiding (Mowrer et al 2014). The extent depends on the surrounding temperature, pH, and dry matter of the excreta, among other factors (Elliott & Collins 1982).…”
Section: Introductionmentioning
confidence: 99%
“…Shifts in the chemical compounds of poultry excreta are initiated immediately after voiding (Mowrer et al 2014). The extent depends on the surrounding temperature, pH, and dry matter of the excreta, among other factors (Elliott & Collins 1982).…”
Section: Introductionmentioning
confidence: 99%